(untitled) - Mishra, D. P. (New Delhi, 2001)
This book introduce about Memoirs of an Indian politician covering the post-1947 period; autobiographical.
Keywords: Chính trị gia,Politicians; Tiểu sử,Biography; Ấn Độ,India